The life of the prophet: lessons and relevance for Muslim managers - Fontaine, Rodrigue Ancelot Harvey (World Academy of Islamic Management, 2022)
his study reviews the life of the Prophet from the perspective of management. Throughout his life, the Prophet stressed that Islam combines the rights of Allah and the rights of the people. This was true whatever the context, whether in Mecca or Madinah, at the beginning or at the end of his career as a prophet, even prior to battles. He stressed that any kind of deception in business is completely rejected. With this is mind, the author presents two trends in management and marketing. Both trends show that the tendency to deceive customers and employees is increasing. However, the pressure for managers of publicly-listed companies to meet the expectations of financial markets is much higher than managers in private enterprises. Two hypotheses are derived and future research is needed to test these hypotheses